2004
DOI: 10.1051/0004-6361:20034102
|View full text |Cite
|
Sign up to set email alerts
|

A study of the expanding envelope of Nova V1974 Cyg 1992 based on IUE high resolution spectroscopy

Abstract: We have carried out a detailed analysis of the IUE archival high resolution spectra of the classical nova V1974 Cyg 1992. The main UV resonance lines show P Cygni profiles in the first days, which change into symmetric pure emission lines, and then slowly become fainter and narrower. Lines of higher ionization species reach their peak luminosity later than those of low ionization. This can be explained by a fast wind which is optically thick in the early days, when the pseudo-photosphere is located inside the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 32 publications
(44 reference statements)
4
45
1
Order By: Relevance
“…Similar resonance-line profiles, including that of Al III, were observed in other ONe, e.g. in IUE spectra of V1974 Cyg (Cassatella et al 2004, their fig. 3), and HST/STIS spectra of V382 Vel (Shore et al 2003, their fig.…”
Section: Uv and Optical Spectroscopysupporting
confidence: 79%
See 2 more Smart Citations
“…Similar resonance-line profiles, including that of Al III, were observed in other ONe, e.g. in IUE spectra of V1974 Cyg (Cassatella et al 2004, their fig. 3), and HST/STIS spectra of V382 Vel (Shore et al 2003, their fig.…”
Section: Uv and Optical Spectroscopysupporting
confidence: 79%
“…All spectra correspond to the epoch when the emission line spectrum was strongest, and roughly represent the same phase of nova outburst development. We note that the nova evolution, including spectroscopic characteristics, scales with t 3 (Cassatella et al 2004;Vanlandingham et al 2001). Here we adopted t 3 = 14 days (Schaefer 2010) for RS Oph, and the values from Cassatella et al (2004), and Vanlandingham et al (2001) 2669 line is also present in the long wavelength IUE spectrum (not shown here).…”
Section: Uv and Optical Spectroscopymentioning
confidence: 78%
See 1 more Smart Citation
“…We favor the latter hypothesis, which is supported by the observations of nova shells soon after outburst. It has been argued in the literature that two distinct outflow components of different origin are present at early times: an earlier, slow one from the circumbinary gas, and a later, fast one resulting from the outburst (see, e.g., Cassatella et al 2004;Williams & Mason 2010). In the case of Nova Cyg 1992, Cassatella et al (2004) show that the main shell ejected at the moment of the outburst contains the bulk of the ejected matter and is located in the outermost region of the ejecta region, while a less massive impulsive event forms a faster-expanding shell that eventually will catch up with the main shell, generating a region of shock interaction where the two shells meet.…”
Section: Dynamics Of the Ejectamentioning
confidence: 99%
“…Interestingly, they found evidence for two distinct shell ejections, the second one of which was ejected with a higher velocity, containing significantly less material. Cassatella et al (2004) suggested that the second ejection was a reaction to the first one as follows. After the ejection of the main shell, the envelope is out of balance and will try to restore equilibrium, but if this does not happen immediately (e.g.…”
Section: A Comparison With Previous Modelsmentioning
confidence: 99%